Mineralogi dan Geokimia Tuf Berumur Tersier dan Kuarter di Daerah Cibadak, Sukabumi, Jawa Barat - Permanadewi, Sam; Maryanto, Sigit; Subandrio, Joko (Jurnal Geologi dan Sumberdaya Mineral, 2017)
Fine-grained pyroclastic rocks  found in the Cibadak area, Sukabumi divided into two groups, namely Tertiary tuff composing of Jampang Formation and Quarternary tuff as the result of  young volcanic eruptions. The relationship between mineralogy and geochemistry of those tuffs are discussed in this paper. Laboratory testing was conducted on fifty rock samples taken from the field. A kind of mineralogy composing the rock can be identified by the XRD (X-Ray Diffraction) mineralogy test, while the major oxide of the rock can be calculated with the XRF (X-Ray Fluorescence) geochemistry test. The XRD mineralogy test shows  two secondary mineral that becomes the differentiation between the two tuffs are zeolites and clay minerals. The zeolites present at most of the Tertiary tuffs as a result of the rock alteration which involves an increasing in formation temperature and pressure. Clay minerals are mostly present at the Quarternary tuffs as a result of rock wheathering on the surface. The zeolite and clay minerals are associated with almost all chemical oxides of the rocks. The chemical oxides including SiO2, Al2O3, Fe2O3, MgO, K2O, TiO, and MnO. The XRF rock-chemically characters show there are no differences of the chemical oxide components on both of these pyroclastic rock groups. Keywords: mineralogy, geochemistry, tuff, Tertiary, Quarternary.